2022
DOI: 10.3390/vaccines10111850
|View full text |Cite
|
Sign up to set email alerts
|

Designing of Peptide Based Multi-Epitope Vaccine Construct against Gallbladder Cancer Using Immunoinformatics and Computational Approaches

Abstract: Gallbladder cancer (GBC) is an aggressive and difficult to treat biliary tract carcinoma with a poor survival rate. The aim of this study was to design a peptide-based multi-epitope vaccine construct against GBC using immunoinformatics approaches. Three proteins implicated in the progression of GBC were selected for B and T cell epitope prediction and the designing of the potential vaccine construct. Seven CTL, four HTL and six Bcell epitopes along with a suitable adjuvant were selected and connected using lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 87 publications
1
2
0
Order By: Relevance
“…Due to the limited success of PIK3CA-directed treatments, patients with the cancers discussed above could potentially experience improved clinical outcomes through a pancancer epitope vaccine targeting prevalent PIK3CA point mutations. Our study considered various clinical variables based on prior studies that served as primary benchmarks when developing our novel epitope selection process [6,7,26,27]. These variables confirmed that AutoEpiCollect's top predicted epitopes were immunogenic, safe, and stable.…”
Section: Introductionsupporting
confidence: 53%
“…Due to the limited success of PIK3CA-directed treatments, patients with the cancers discussed above could potentially experience improved clinical outcomes through a pancancer epitope vaccine targeting prevalent PIK3CA point mutations. Our study considered various clinical variables based on prior studies that served as primary benchmarks when developing our novel epitope selection process [6,7,26,27]. These variables confirmed that AutoEpiCollect's top predicted epitopes were immunogenic, safe, and stable.…”
Section: Introductionsupporting
confidence: 53%
“…These tools enable epitope mapping, structural design, and molecular interaction studies critical for effective vaccine development. Leveraging immunoinformatic approaches, numerous vaccines have been successfully developed against various infections and cancers [16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…In another study, Kumar et al (2022) incorporated the epitopes from L1, E5, E6, and E7 oncoproteins of HPV 16 and HPV 18 to formulate a chimeric peptide-based vaccine to combat cervical cancer [ 18 ]. Dar et al (2022) implemented a reverse vaccinology approach to determine the immunogenic B, CTL, and HTL epitopes from NT5E, ANPEP, and MME proteins, the putative targets for gallbladder cancer (GBC), and developed a robust peptide-based vaccine against GBC [ 19 ]. Importantly, our team successfully developed an immunoinformatics-based peptide vaccine targeting SOX9, a transcription factor that has been reported as a major regulator of TNBC metastasis [ 20 ].…”
Section: Introductionmentioning
confidence: 99%